14-3(5x-12)+1=4-(20x+1)

Notice: Undefined variable: position6 in /home/domains2/public_html/painphr.com/show.php on line 143

Guide :

# 14-3(5x-12)+1=4-(20x+1)

solve for x

## Research, Knowledge and Information :

Notice: Undefined variable: go_page in /home/domains2/public_html/painphr.com/show.php on line 211

### 14-3(5x-12)=4x-(20x+1) - Get Easy Solution

Simple and best practice solution for 14-3(5x-12)=4x-(20x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to ...

### how do you solve 20 (3/5x + 1/4) = (7/20x-4)20 - Brainly.com

how do you solve 20 (3/5x + 1/4) = (7/20x-4)20 - 2031657 ... Hi there! Have questions about your homework? At Brainly, there are 60 million students who want to help ...

### 1. 20x-1=14 2. 2(x+6)=(2x+12) 3. 8t-21=2t-7 4. 0.5 ... - Chegg

Answer to 1. 20x-1=14 2. 2(x+6)=(2x+12) 3. 8t-21=2t-7 4. 0.5x-0.2(50 ... home / study / math / algebra / algebra questions and answers / 1. 20x-1=14 2. 2(x+6)=(2x+12 ...

### Linear Equation Theory and Problems - Math

... {5x - 4}{2} = \frac{0.5x + 1}{3}$B)$1 –\frac{x - 3}{5} ... x = 12 + 2=> 14x = 14 => x = 1 B) \$1 – \frac{x - 3}{5} = \frac{3(1 ... 5x 2 - 4 + 20x + 58 = 0 ...

### 6x +2(x-1)=14 -3+4( X+3)=5 6 - 2 (d +4)=6 5+7(x+3 ... - Chegg

3( x - 4) + 3x= 7 - 2( x -1) 9 lessthan y the sum of two thirds ofn and n product of 9 and4 more than x

### Answer Math Problems | Math Problem Solver | Help with Math ...

A large number of objective answer math problems are solved here to help the ... 4. Simplify: (4x 2 + 5x) + (x 2 - 5x + 1) Solution: (4x 2 ... (-5) 2 - 4 × 3 × 1 ...

### 3.2 The Factor Theorem and The Remainder Theorem

2 1 4 5 14 2 12 14 1 6 7 0 We have ... 3.2 The Factor Theorem and The Remainder Theorem 261 ... According to Theorem3.4, we have 5x3 2x2+1 = (x 3) 5x2 + 13x+ 39 +118.

## Suggested Questions And Answer :

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### y=-x^2+35x

We find the x-intercepts by setting y to zero. -x^2 + 35x = 0 x^2 - 35x = 0 We use "completing the square." x^2 - 35x + (35/2)^2 = (35/2)^2 x^2 - 35x + 17.5^2 = 17.5^2 (x - 17.5)^2 = 17.5^2 x - 17.5 = ±17.5 x = 17.5 ±17.5 x = 17.5 + 17.5    and    x = 17.

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### equation of a line through (0,6) and perpendicular to 35x-7y=-7

other line: 35x-7y=-7 bekum y=5x+1 its slope=+5 line yu want=90 deg so its slope=-1/5=-0.2 point=(0,6), so y-intersept=6 y=-0.2x +6

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### 6x+y−z=−3 ; 29x+5y+3z=6 ; 35x+6y+2z=3

Call the three equations A, B and C. Note that if we double C we get the same constant 6 as B. So we can write B=2C. That is, 70x+12y+4z=29x+5y+3z. So 41x+7y+z=0. Similarly, note that A=-C. That is, 6x+y-z=-35x-6y-2z. So 41x+7y+z=0. And B=-2A: 29x+5y+3z=-12x-2y+2z, or 41x+7y+z=0. So, because we've i

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### "solve for x in the equation 4x(x-8)-5x(x-7)=-4"

4x (x-8) - 5x (x-7) = -4 original line 4x^2 - 32x - (5x^2 - 35x) = -4 multiply out the two brackets with the outside of the brackets 4x^2 -32x - 5x^2 + 35x = -4 take out the second bracket fully by timesing by negative (swapping signs) -x^2 +3x +4 = 0 gathering all terms together and adding 4 to

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how do you solve X⁴-35X²-36=0.

x^4 - 35x^2 - 36 = 0 ( x^2 + 1 ) ( x^2 - 36 ) = 0 ( x^2 + 1 ) ( x^2 - 6^2 ) = 0 ( x^2 + 1 )(x + 6)(x - 6 ) = 0 x = 6 and x = - 6

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### 3x/4-2/7-x/3-1=0

3x/4-2/7-x/3-1=0 x(3/4-1/3)-(1+2/7)=0 x(9/12-4/12)-(7/7+2/7)=0 5x/12-9/7=0 5x/12=9/7 35x=9.12 x=9.12/35=108/35

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### solve equation

me thank that garbage shood be (6/x) +5 -[(9/x) -5] = [(15/x^2) -25] bekum: 6x +5x^2 -(9x -5x^2) +25x^2 -15=0 or 6x +5x^2 +5x^2 -9x +25x^2 -15=0 (5x^2 +5x^2 +25x^2) +6x -9x -15=0 35x^2 -3x-15=0 quadratik equashun giv roots=0.698912143 & -0.613197857 b^2-4ac=2109, sqrt(2109)=45.923850013

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### sqaure root of 7x+1 -square root x-5 =6

sqrt(7x+1) - sqrt(x-5) = 6 a + b = c a^2 + 2ab + b^2 = c^2 (7x+1) +2 * sqrt(7x+1) * sqrt(x-5) + (x-5) = 36 2 * sqrt(7x+1) * sqrt(x-5) + 8x - 4= 36 2 * sqrt(7x+1) * sqrt(x-5) = -8x + 40 a * b * c = d a^2 * b*2 * c^2 = d^2 4 * (7x+1) * (x-5) = (-8x + 40)^2 4 * (7x^2 + x - 35x -5) = (-8x + 40)

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### find all real solutions of the equation. 1/x^3+ 8/x^2 + 16/x=0

Notice: Undefined variable: position4 in /home/domains2/public_html/painphr.com/show.php on line 277

### how do you factor f(x)=3x^3+4x^2-35x-12 ; 3

how do you factor f(x)=3x^3+4x^2-35x-12 ; 3 divide the 3 root out remember that the root has the opposite sign           _3x^2 + 13x + 4______ x - 3) 3x^3 + 4x^2 - 35x - 12          3x^3 - 9x^2 &nb

#### Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question

Notice: Undefined variable: position5 in /home/domains2/public_html/painphr.com/show.php on line 357
• Start your question with What, Why, How, When, etc. and end with a "?"
• Be clear and specific
• Use proper spelling and grammar